(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this study was to determine whether there was an effect of the discovery learning model assisted by Prezi media on mathematics learning outcomes in terms of learning styles, whether the mathematics learning outcomes of students who used the discovery learning model assisted by Prezi media were better than students who used conventional learning models. The sampling technique used was cluster random sampling. The data collection technique used was the test method and non-test method. Based on the prerequisite test, it was concluded that the samples were normally distributed, had the same variance, and had the same initial ability. Based on the results of the ANOVA analysis of two different cell lines conducted by researchers, it can be seen that the main effect of A (learning model) the statistical value of the test is and .. So that which results in the null hypothesis being rejected. Thus it can be concluded that there are differences in the effect of the DL learning model assisted by Prezi media and the conventional learning model on student mathematics learning outcomes.